THE THE EFFECT OF HCl ACTIVATOR CONCENTRATION ON THE EFFECTIVENESS OF ACTIVATED CARBON DERIVED FROM CORNCOBS FOR METHYLENE BLUE ADSORPTION - Setyaningrum, Dyah; Fajarwati, Novia; Maghfiroh, Amalia (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2024)
This study aimed to investigate how activator hydrochloric acid (HCl) concentration affects the adsorption capacity of corncob-activated carbon in Methylene Blue (MB) dye.  This was followed by immersion in HCl solutions with various concentrations (2.5 M; 3M; 3.5 M; and 4 M) as chemical activating agents. Next, FTIR and XRD were used to characterize the activated carbon that had been activated and unactivated. The study analyzed the reduction of methylene blue dye concentration in the air to evaluate the effectiveness of activated carbon as an adsorbent. It examined various factors influencing the adsorption process, including different initial concentrations of the azo dye (20 ppm, 30 ppm, 40 ppm, 50 ppm, and 60 ppm) and contact times (15, 30, 45, and 60 minutes). The experimental results indicated that a 3 M concentration of HCl was the most effective activator, leading to a maximum dye removal rate of 80.77%. For an initial concentration of 20 ppm of the azo dye, the highest adsorption results were achieved at 85.67%. Furthermore, the optimal contact time for maximum adsorption was found to be 30 minutes, with a peak adsorption rate of 70.08%. The Langmuir adsorption isotherm model demonstrated a better fit for the adsorption of methylene blue onto corncob-activated carbon. It can be concluded that activated carbon produced from corn cobs and treated with HCl is an effective adsorbent for reducing methylene blue levels in the solution.